2021
DOI: 10.1038/s41598-021-82635-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential salivary biomarker panels for oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most prevalent cancers worldwide with the maximum number of incidences and deaths reported from India. One of the major causes of poor survival rate associated with OSCC has been attributed to late presentation due to non-availability of a biomarker. Identification of early diagnostic biomarker will help in reducing the disease morbidity and mortality. We validated 12 salivary proteins using targeted proteomics, identified initially by relative quantification … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Initially, 93 proteins were found, and up to 30 overexpressed were selected, and CD44, S100A7, and S100P were significantly associated as putative candidates for the early phase of tumor progression [ 41 ]. Aiming to differentiate the early to the late phase of OSCC patients, more recently, Jain et al, individuated from saliva samples several proteins by LC-MS in oral squamocellular cell cancer and thereafter twelve were validated using targeted proteomics [ 42 ]. Among these, Alpha 2 Glycoprotein 1 (AZGP1), Alpha-2-Heremans-Schmid Glycoprotein (AHSG), Keratin 6C (KRT6C) and BPI fold-containing family B member 2 (BPIFB2) showed high sensitivity and specificity, suggesting theirs as a potential salivary biomarker of different stages of OSCC [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Initially, 93 proteins were found, and up to 30 overexpressed were selected, and CD44, S100A7, and S100P were significantly associated as putative candidates for the early phase of tumor progression [ 41 ]. Aiming to differentiate the early to the late phase of OSCC patients, more recently, Jain et al, individuated from saliva samples several proteins by LC-MS in oral squamocellular cell cancer and thereafter twelve were validated using targeted proteomics [ 42 ]. Among these, Alpha 2 Glycoprotein 1 (AZGP1), Alpha-2-Heremans-Schmid Glycoprotein (AHSG), Keratin 6C (KRT6C) and BPI fold-containing family B member 2 (BPIFB2) showed high sensitivity and specificity, suggesting theirs as a potential salivary biomarker of different stages of OSCC [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our data, AZGP1 was considered to have a significant impact on KIRC, KIRP, UCEC, and UVM prognosis, but it has been shown that AZGP1 could be a feasible candidate biomarker for colorectal cancer based on an analysis of the GSE21962, GSE24551, and GSE29638 datasets in the GEO(Gene Expression Omnibus) database ( 24 ). Patients with oral squamous cell carcinoma (OSCC) have low salivary levels of AZGP1 ( 25 )and low mRNA levels of AZGP1 in OSCC tumor tissues ( 26 ). The role of AZGP1 in inhibiting cell invasion and migration ( 27 , 28 ) suggests its correlation with poor disease response.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of the use of salivary biomarkers is related to their reduced concentrations (100–1000 fold) compared to plasma, but this aspect is not particularly crucial in the detection of OSCC because these molecules are secreted locally in the proximity of the primary tumor [ 49 ]. On the other hand, the standardization of salivary tests requires high specificity and sensitivity of the selected molecules [ 50 ] in order to differentiate PMOLs and OSCC from other inflammatory conditions, such as gingivitis, periodontitis or infections that might affect the levels of salivary biomarkers [ 51 ]. The presence of inflammation could result in false-positive responses, reducing the diagnostic value of the biomarkers in PMOLs and OSCC.…”
Section: The Role Of Saliva In Oral Cancer Detectionmentioning
confidence: 99%